The Effect Of Ball Feeling Training On The Dribbling Ability Of Futsal Extracurricular Students At Sma It Ar Raihan Bandar Lampung - Jihad Akbar; Tarigan, Herman; Candra Kurniawan; Nurseto, Frans (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to determine the effect of ball feeling training on the dribbling ability of futsal extracurricular students at SMA IT Ar-Raihan Bandar Lampung. Dribbling is one of the important basic techniques in futsal that requires good ball control. However, there are still many students who have not been able to dribbling optimally. Ball feeling training is believed to be able to improve ball control and player sensitivity to the ball while playing. This study used a quasi-experimental method with a preTest-postTest control group design. The research subjects were 22 students who were divided into two groups, namely the experimental group (ball feeling training) and the control group. The research instrument used a zig-zag dribbling Test to measure dribbling ability before and after treatment. The results of the t-Test showed that there was a significant effect on the experimental group with a calculated t value = 4.884> t table = 2.228, which means that ball feeling training significantly improved students' dribbling ability. In contrast, the control group did not show a significant increase with a calculated t value = 0.634 <t table = 2.228. In addition, the comparison Test between the two groups in the final Test showed a significant difference with a calculated t value = 4.114 > t table = 2.086. This finding proves that ball feeling training is effective in improving dribbling skills in adolescent futsal players.